Tension–tension fatigue behaviour of woven flax/epoxy composites. (June 2015) - Asgarinia, Soroush; Viriyasuthee, Chanvit; Phillips, Steven; Dubé, Martine; Baets, Joris; Van Vuure, Aart; Verpoest, Ignaas; Lessard, Larry
Understanding the fatigue performance of biocomposites is critical in order to increase their acceptance, but current literature in this area is mostly limited to nonwoven reinforcements. This paper considers the tension–tension fatigue of three different woven flax/epoxy composites, for which two of them are prepreg-based and the other is manufactured using the Vacuum Assisted Resin Transfer Moulding (VARTM) process. Good fatigue performance of flax fibres comparable to those exhibited by glass fibres has shown the potential of this material to be implemented in load-bearing applications. The results suggest that minimizing the crimp in the yarns is a major concern to increase the resistance to fatigue damage in this class of materials. In addition to the three mentioned composites, two hybrids of flax/glass/epoxy were manufactured using the same VARTM process to check if the fatigue stability of flax fibre is extendable to its hybrids. The results show that an increase in the strength is possible, while maintaining similar fatigue behaviour as the plain flax/epoxy composites.